RESPONSE OF CAULIFLOWER PLANTS TO SPRAY WITH NUTRIENTS SOLUTIONS FROM DIFFERENT SOURCES - Hussein, M. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out at experimental field of Horticulture and Landscape Department – College of Agriculture – Baghdad University, during autumn season of 2014. This experiment was aimed to study the effect of foliar spray with algae extract (Algaton-20) at two concentrations (2 and 4ml.L-1) and liquid mineral nutrient (Fosfital calcium) at two concentrations (3 and 6ml.L-1) and the water extract of dry seeds of broad bean at two concentrations (2.5 and 5g.L-1) as different sources of nutrition elements (Mo,B,Ca,K,P,N) beside control treatment in vegetative growth and the nutrition content of curds and production parameters of cauliflower plants cv.Eearly snowball.The study was conducted according to Randomized Complete Block Design with three replications. The results are shows a significant differences between spraying nutrients solutions and control treatment in all parameters studied, spraying with Algaton-20 (2 ml.L-1) was recorded higher number of leaves.plant-1 and length of petiole and sulfur content in curds while spraying with(4ml.L-1) estimated higher length of assimilative surface and percentage of dry matter and boron content in curds. Spraying with water extract of dry broad bean seeds with (5g.L-1) led to record biggest leaf area and higher content of curds from nitrogen and molybdenum. While spraying with(2.5g.L-1) led to record higher dry weight of vegetative growth and the content of curds from phosphorus and potassium and weight of curds which estimated 0.662 Kg and total weight of plant which estimated 0.679Kg and total yield which estimated 24.33ton.ha-1 compare to control treatment. which meaning that using nutrients from organic and natural source will improve the nutrition values with medicinal importance of the produce with environment less pollution.